From Industrial Relations to the Employment Relationship: The Development of Research in Britain - Edwards, P. K. (Relations industrielles / Industrial Relations, 1995)
In contrast to gloomy diagnoses of the state of industrial relations in the US, the situation in Britain is comparatively healthy. Reasons include the way in which the human resource management (HRM) challenge was met and the intellectual development of the subject from old industrial relations towards a deeper analysis of the employment relationship. These reasons are closely connected to the continuation of a case study tradition of research. Examples of such work illustrating this analysis, particularly those exploring management and the nature of HRM, are discussed. A future research agenda comparing national regimes of labor regulation is sketched.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; History; Human resource management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies